Kamus Saku Praktis untuk Pelajar Indonesia: Memahami Istilah Ilmiah Biologi dalam Bahasa Inggris (Bilingua, 2024)
This article outlines the development of a bilingual pocket dictionary specifically designed for Indonesian junior high school students to aid in learning biological scientific terms in English. Using a descriptive research approach, the dictionary was crafted from English terms extracted from widely used junior high school natural science textbooks. These terms were translated into Indonesian and provided with clear, concise bilingual definitions. To enhance understanding, simple illustrations and example sentences were included. The dictionary is designed to be compact and user-friendly, making it a practical tool for students to carry and use as a reference. By addressing the linguistic barriers in learning biology, this dictionary not only simplifies the learning process but also promotes scientific literacy and bilingual proficiency. This project represents a critical step in supporting science education in Indonesia, providing a resource that bridges the gap between complex scientific vocabulary and students' language skills.